EDUCATION CHARACTER VALUES IN TRADITION SAYYANG PATTU'DU IN POLEWALI MANDAR - Maksum, Muh. Nur Rochim; Ramdhani, Deddy; Bansu, Ikhlima Yaumil Fitri (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
The value of character education can be extracted from cultural characteristics that are in harmony with the characteristics of the local community, including the value of character education can be explored in the tradition of sayyang pattu'du in Polewali Mandar. This research aims to find out the process of implementing the tradition of sayyang pattu'du in Polewali Mandar, and the values of character education contained in the tradition of sayyang pattu'du in polewali mandar. This research paradigm is qualitative with a type of field research as well as a phenomenological approach. The process of collecting data is carried out with observation, interviews, and documentation. Data analysis includes data reduction, presentation of data, and conclusion withdrawal. The result of this study is sayyang Pattu'du has the meaning of dancing horses or animals taught with dance movements. This tradition is a form of appreciation from parents to their children when they have khatam al-Qur'an, The process of implementing the tradition of sayyang pattu'du begins during the day, the child comes to the mosque with a horse that has been decorated in such a way and then marches in order. The procession route starts from the mosque then continues by circling the village. The values of character education contained in the tradition of sayyang pattu'du are religious, disciplinary values, hard work values, values of appreciating achievement, friendly/communicative values, values of reading, values of social care, values of responsibility.